Implementasi Kurikulum Merdeka di SMK Negeri 1 Lhoknga - Anita, Anita; Haeruddin, Haeruddin; Akhmad, Akhmad (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study investigates the implementation of the Independent Curriculum (Kurikulum Merdeka) at SMK Negeri 1 Lhoknga, a vocational high school in Aceh, Indonesia. The Independent Curriculum aims to foster student-centered learning, character development, and competency-based education. However, its practical application at vocational institutions remains understudied. This research explores how the curriculum is implemented, the challenges encountered, and the strategies employed to overcome them. A qualitative descriptive approach was used, involving interviews with school leaders, teachers, students, and parents; classroom observations; document analysis; and questionnaires. The findings reveal that the school has made considerable efforts to adapt the curriculum through project-based learning, differentiated instruction, and the development of students’ character in alignment with the Pancasila Student Profile. Nevertheless, challenges such as limited facilities, inconsistent teacher readiness, and low student motivation persist. In response, the school has initiated capacity-building programs for teachers, collaborated with industry partners, and promoted participatory learning strategies to improve student engagement. This study highlights the importance of institutional support, continuous teacher training, and stakeholder collaboration for successful curriculum implementation. The findings provide practical insights for other vocational schools facing similar transitions and contribute to the broader discourse on curriculum reform in Indonesia’s educational system.